Newly qualified health visitor: Staff wellbeing and delivering an effective service. (2nd January 2019) - Bewick, Jessica
Abstract : Now in the fourth week of working for a new Trust, Jessica Bewick has discovered the impact of support for staff wellbeing on the health visiting service